Output-Based Aid for Water Supply in Uganda : Increasing Access in Small Towns - Azuba, Chris; Mugabi, Josses; Mumssen, Yogita (World Bank, Washington, DC, 2012)
In Uganda small private companies have been operating water supply systems since 2001. A pilot output-based aid (OBA) project is expanding this approach. The project is leveraging private sector finance and expertise to provide access to piped water for an estimated 45,000 people in small towns and rural growth centers while increasing efficiency and accountability in the use of funds. About 8,100 people have benefited so far, and the Government is exploring the use of OBA approaches as part of its national framework for water supply.